EUROPEAN VEGETATION SURVEY - FROM THE METHODOLOGICAL DISCUSSION TO THE FIRST APPROXIMATION - PIGNATTI, S.; DOMINICI, E.; PIETROSANTI, S. (Annali di Botanica, 1997)
The methodological basis of phytosociology is discussed. This method for the study of vegetation was first proposed by Braun-Blanquet for the analysis of the floristic structure of plant communities and their synecology, but in the last decades floristic data have been emphasized, whereas ecological factors were more and more neglected. When the association is described only by floristic data, it appears as a chaotic system. New methods for vegetation analysis are described, based on the complementarity of floristic and synecological data. The use of the fingerprint approach to express ecological factors is discussed. It is proposed to construct the Vegetational Information System dedicated to the survey of plant communities in Europe. A model is proposed.